Water Resources Management Select Proceedings of ICWEES-2016 (Water Science and Technology Library,, 2018)
This book contains two parts. The first part deals with some aspects of irrigation, encompassing farm irrigation systems, landscape gardening, energy assessment for drip irrigation, and micro-sprinklers. The second part is on water resources planning and management. It discusses water crisis, challenges in river health management, water supply systems, salt water intrusion, lake management, water supply demand assessment, integrated water resources management, among other topics. The book will be of interest to researchers and practitioners in the field of water resources, hydrology, environmental resources, agricultural engineering, watershed management, earth sciences, as well as those engaged in natural resources planning and management. Graduate students and those wishing to conduct further research in water and environment and their development and management may find the book to be of value.